How did we find out about nuclear power? - Asimov, Isaac, 1920-; Wool, David (New York : Walker, 1976)
Traces the work of many scientists over more than one hundred years in developing man's knowledge of nuclear power.
Includes index.
Keywords: Nuclear energy -- Juvenile literature; Nuclear energy